Developing A Framework for Inclusive Community-Driven Rural Tourism Through Resident’s Citizenship Behaviors (S/O 14880) - Shaari, Hasnizam; Ahmad, Norzieiriani; Perumal, Selvan; Sulaiman, Yaty; Saad, Shahrin; Ibrahim, Johan Afendi (UUM, 2023)
Destination branding such as rural tourism had gained interest from various parties, including academicians, practitioners, governments, and other stakeholders. Hence, this study aims to examine how residents perceived the impact of rural tourism and place branding influences their voluntary behavior for the success of the rural tourism agenda. This study employs a mixed-sequential method. The findings from the focus group discussion revealed five major type of residents’ citizenship behaviors. The survey among 380 respondents from selected rural tourism attractions found that attitude toward cultural, social, perceived place branding, and resident involvement significantly affect resident citizenship behaviors. Besides, the moderation and mediation interaction was also detected in this study. This study contributes to bridging the gaps, especially in residents/community support for rural tourism. An inclusive community-driven rural tourism model was introduced at the end of this report together with few managerial implications.